Liberatory Music Therapy Model of Gender Affirming Voicework - Maevon Gumble; Braedyn Inmon; Kaylynn Schachner (Voices, 2025)
Since initial explorations of gender affirming voicework within the field of music therapy were first offered (Gumble, 2019a, 2019b, 2020), the authors have collaborated to further develop this work. From this collaboration, a specific set of ideas were collected to delineate a liberatory approach to working with gender and the voice within music therapy. These are presented as the Liberatory Music Therapy Model of Gender Affirming Voicework (LMT-GAV). The intention of this article is to integrate experiences the authors have had thus far and to (a) provide a definition, (b) summarize theories, methods, models, and concepts that are foundational to the model, and (c)delineate scope of practice.